Możliwości biologicznej ochrony roślin przed chorobami w szkółkarstwie, ze szczególnym uwzględnieniem lęgniowców (Oomycetes) i grzybów z rodzaju Fusarium - Okorski, Adam; Nowakowska, Justyna; Oszako, Tomasz; Pszczółkowska, Agnieszka (Leśne Prace Badawcze, 2014)
Achieving high quality propagative material is difficult today due to the limited number of pesticides recommended for use. Simultaneously, EU regulations on Integrated Pest Management (IPM) in forest nurseries came into a force, requiring a search for alternative plant protection methods that are safe for humans, animals and the environment. In this paper, we present the possibilities of using bio-fungicides against diseases in forest nurseries, their mechanisms of action, as well as the direction of their development (according to IPM rules). We reviewed the results achieved by different research teams presenting the possibilities and trends in combatting Oomycetes and Fusarium spp. pathogens currently having the most important economic impact.